The Urgency of Law Establishment Regarding Block-Chain Technology in Indonesia Based on the Perspective of Dignified Justice (Keadilan Bermartabat) - Prasetyo, Teguh; Karo Karo, Rizky P.P.; Pricilia, Vena; Setiadinata, Natasha (Universitas Kuningan, 2019)
AbstractBlock-chain technology has been utilized in various countries in the world, specifically in Indonesia. Block-chain brings positive impact on the development of businesses in Indonesia, but it also has negative impacts if the government of Indonesia doesn’t keep an eye on it. The Positive impacts are that block-chain can improve the efficiency of time and transactions fee. But on the other hand, block-chain gives opportunity to the beginning of cybercrime, for example data theft, client’s financial data. The formulation of problems are: 1. What is the urgency of the establishment of law concerning block-chain technology utilization in Indonesia based on the perspective of dignified justice; 2. What kind of legal protection should be established concerning consumer and business founder protection on the utilization block-chain technology. This research method is a normative empirical method conducted the way of analyzing norms, the laws and regulation on regarding the topic and with profound interviews with experts/officials who has decent knowledge in this specific area. The purpose of this research is to analyze the consumer and founder protection related on the usage of block-chain and to give an input to the ministry on the urgency of the formation of the law on blockchain in Indonesia. The results of this study are that the blockchain technology has been used in various businesses, such as financial / banking sector, agriculture, etc. Blockchain technology can change the paradigm in the financial sector from a centralized system to a decentralized system and to improve system security. Blockchain must be monitored because the blockchain system contained data privacy, financial privacy to prevent the criminal acts. The conclusion is that the supervision of the blockchain system is carried out by forming special regulations on the blockchain or adding new norms which are based on the dignified justice about blockchain in Bank Indonesia Regulations or Financial Services Authority Regulations related to financial technology.Keywords: Blockchain, Consumers Protection, Money Laundering, Renewal Law, Justice Dignity (Keadilan Bermartabat)Urgensi Pembentukan Peraturan Perundang-Undangan Terkait Teknologi Blockchain di Indonesia berdasarkan Keadilan BermartabatAbstrakTeknologi blockchain telah banyak dimanfaatkan di berbagai negara di dunia, khususnya di Indonesia. Penggunaan blockchain membawa dampak positif bagi pengembangan dunia bisnis di Indonesia, namun juga memiliki dampak negatif jika tidak diawasi oleh baik oleh Pemerintah Indonesia. Dampak positif penggunaan blockchain dapat meningkatkan efisiensi waktu, biaya lalu lintas transaksi keuangan. Namun disatu sisi, blockchain menimbulkan dampak negatif yakni membuka peluang munculnya kejahatan dunia maya (cybercrime) misalnya pencurian data privasi, data keuangan nasabah. Adapun yang menjadi rumusan masalah adalah: 1. Apakah yang menjadi urgensi pembentukan peraturan perundang-undangan terkait manfaat teknologi blockchain di Indonesia berdasarkan perspektif keadilan yang bermartabat; 2. Apa jenis perlindungan hukum yang perlu dibangun tentang perlindungan konsumer dan pelaku usaha dalam penggunaan teknologi block chain. Metode yang digunakan ialah normatif empiris yang dilakukan dengan cara menganalisis norma, peraturan perundang-undangan terhadap topik yang diangkat dan dengan metode wawancara yang mendalam kepada narasumber/pejabat yang memiliki kompetensi di bidang tersebut. Tujuan penelitian untuk menganalisis perlindungan konsumen pelaku usaha terkait penggunaan blockchain dan untuk memberi masukan bagi Kementerian terkait tentang urgensi pembentukan peraturan penggunaan blockchain di Indonesia. Hasil penelitian ini adalah teknologi blockchain telah dipergunakan di pelbagai usaha, baik di sektor keuangan/perbankan, pertanian dan lain sebagainya. Teknologi blockchain dapat merubah paradigma di sektor keuangan dari sistem sentralisasi menuju sistem desentralisasi dan untuk meningkatkan keamanan sistem. Blockchain wajib diawasi karena di dalam sistem blockchain terdapat privasi data, privasi keuangan dan agar tidak disalahgunakan untuk melakukan tindak pidana. Kesimpulannya adalah pengawasan sistem blockchain dilaksanakan dengan membentuk peraturan khusus tentang blockchain atau menambahkan norma baru yang berprinsipkan keadilan bermartabat tentang blockchain dalam Peraturan Bank Indonesia ataupun Peraturan Otoritas Jasa Keuangan yang terkait teknologi finansial. Kata Kunci: Blockchain, Perlindungan Konsumen, Pencucian Uang, Pembaharuan Hukum, Keadilan Bermartabat